Determination of Acid-Extractable Phenols and Organochlorine Pesticides in Laguna Lake by Gas Chromatography-Mass Spectrometry - Dancel, Maria Cristina A (Archīum Ateneo, 1998)
The presence of eight acid-extractable phenols and sixteen organochlorine pesticides (OCPs) in Laguna Lake water was determined. The acid-extractable phenols which were analyzed included: phenol, 2-chlorophenol, 2-nitrophenol 2,4-dichlorophenol, 4-chloro-3-methylphenol, 2,4,6-trichlorophenol, 4-nitrophenol, and pentachlorophenol. The OCPs were as follows: α-BHC, β-BHC, γ-BHC (lindane), δ-BHC, heptachlor, aldrin, heptachlor epoxide, endosulfan I, 4,4'-DDE, dieldrin, endrin, endosulfan II, 4,4-DDD, endrin aldehyde, endosulfan sulfate, and 4,4-DDT.Water samples trom five different sites in Laguna Lake were collected in October and November 1996, and February and May 1997. The phenols and OCPs were extracted separately by liquid-liquid extraction. Identification and quantification were done by capillary gas chromatography-mass spectrometry (GC-MS). None of the sixteen OCPs was detected in any of the water samples. On the other hand, phenol and 4-nitrophenol were detected in some samples collected in February and May 1997. These analytes, however, could not be quantified because they were below this study's practical quantification limits (PQL) of 1.8 µg/L for phenol and 1.2 µg/L for 4-nitrophenol. The PQLs were based on the actual method detection limits (MDL) of the acid-extractable phenols and OCPs.